Recessed nanoband electrodes fabricated by focused ion beam milling - Lanyon, Y.; Arrigan, Damien (Elsevier SA, 2007)
This paper describes the fabrication of band electrodes and electrode arrays recessed within nanoscale trenches sculpted in silicon nitride passivation layers by focused ion beam (FIB) milling, thus creating recessed nanoband electrodes. Controllable nanoband dimensions, numbers and inter-band spacing have been rapidly created by the direct write approach of the FIB milling technique. Milling of cross-sections through the trenches demonstrated that the trench walls were non-vertical and enabled evaluation of the trench wall angle, ca. 19?. Cyclic voltammetric characterisation using a simple redox probe ion, ferrocene carboxylate in phosphate buffered saline electrolyte solution, demonstrated steady-state voltammetric curves, consistent with multi-dimensional diffusion being the controlling mass transport mechanism under these conditions. The simplicity of the preparation method for these nanoband devices provides scope for their use in sensing applications as well as in fluid transport studies in nanodimensions.